Playful learning for information literacy development. (June 2020) - Walsh, Andrew
Play is often seen as frivolous, childish, suitable only for young children. In contrast, this paper will discuss the idea that using playful learning approaches is often a good fit for the development of information literacy in all ages. To do this, it will outline the meaning of information literacy that the author takes, explain where playful learning is placed within learning theories and pedagogies, and show why and how they fit together. Examples of playful practice in library and information literacy training will be given to illustrate current practice, together with gaps within that practice. It will briefly address some of the barriers to using playful learning approaches in information literacy development, and offer some ways forward for information literacy practitioners.